Quantitative food webs and invertebrate assemblages of a large River: A spatiotemporal approach in floodplain shallow lakes - de Azevedo Carvalho, Débora (2016)
To test the hypothesis that the hydrological regime of large Rivers affects the structure of invertebrate communities and food webs in floodplain lakes, we studied invertebrate assemblages and stomach contents of fish and decapods in two shallow lakes in the Paranć River floodplain, Argentina, with different connectivity (indirect and permanent, IPC; direct and temporal, DTC) to the fluvial system over three hydroperiods (flooding, transition, drought). Invertebrate assemblages exhibited temporal variation, with higher dissimilarity during the drought phase. However, zooplanktonic and pleustonic attributes varied spatiotemporally, and were better explained by other environmental variables. The food webs in the two lakes differed, with higher connectance and fewer predators in the DTC Lake. In general, the use of trophic resources by fish and decapods reflected the local and abundant resources in the system. The persistence of communities in floodplain lakes with temporary connectivity to the river may relate to the foraging decisions of consumers to buffer environmental fluctuations. The consumption of abundant resources highlighted the importance of autochthonous inputs into floodplain lakes. However, the variation in food supply as a key factor governing food-web structure and stability should be further investigated. Journal compilation.